Assessment of the Edo State of Nigeria tractor hiring services (2006)
A study was undertaken to assess the tractor-hiring unit of Edo state, Nigeria. The criteria used were fleet of equipment, personnel and workshop facilities and its impact on the farming populace in the state. The study adopted the use of a questionnaire and interview schedules. Among the information requested from the respondents were access to services rendered by the unit and increment in farm sizes. Records available at the headquarters and zonal offices of the unit provided additional sources of information. The unit has seven Steyr, 18 Fiat and nine Massey Ferguson tractors, eight ploughs, 17 harrows, seven tipping trailers, two boom sprayers, one fertilizer spreader, three maize shellers, two rotary slashers, one drilling machine, two ridgers and a pick-up van which are located in the various zones of the unit. Most of these equipment are either functional or require minor repairs to be used on the field. There is sufficient number of tractors but insufficient implements to fully utilize them. Workshop facilities and personnel are inadequate. The maintenance culture adopted is customer motivated. This is not a good practice as it has resulted in about 12% of the equipment being abandoned as scraps. There has been a general increase in farm sizes since the introduction of the unit. Some old time peasant farmers have been able to increase the sizes of their cultivated farmlands from below 2.5ha to between 5 and 10ha, while the aggressive new entrants have also been able to establish sizeable farms of over 25ha. This has considerably increased their economic fortunes. Some farmers have however not benefited from the activities of the unit. Three reasons account for this, and these are inability to raise the cost of hiring, the remoteness of their farms, which make them inaccessible to farm machinery and their small holdings, usually below 2.5ha, for which the use of farm machinery is unprofitable. The unit has great potentials for improving the agricultural productivity of the state if the equipment available can be effectively utilized. Recommendations made towards achieving this goal include adoption of regular maintenance culture; staff recruitment, retraining and motivation; upgrading of workshop facilities and establishment of new ones in the zones, and adequate funding by the state government.